KNOWLEDGE LEVEL OF NU MA'RUF KUDUS HIGH SCHOOL STUDENTS REGARDING COMPOST FERTILIZER TO SUPPORT SUSTAINABLE AGRICULTURAL EFFORTS - M. Aris Pujiyanto; Dwi Putriana Nuramanah Kinding; Muhamad Solekan; Sarno Sarno (Universitas Perjuangan Tasikmalaya, 2024)
The waste problem is one of the big challenges faced by communities throughout the world. The environmental impacts of the waste problem include water and air pollution, ecosystem damage, and reduction of natural resources. This research aims to analyze the level of knowledge of NU Ma'ruf Kudus High School students about compost fertilizer, the manufacturing process, and the benefits of compost fertilizer. The research method used is descriptive analysis using a questionnaire as a data collection tool. The respondents of this research were 30 class XII students of SMA NU Ma'ruf Kudus. The data analysis used is a Likert scale. The research results showed that the level of students' knowledge about compost fertilizer, the manufacturing process and its benefits increased after being given education. Most students have a good understanding of the concept of compost fertilizer and its benefits in sustainable agriculture. These findings indicate that there is still a need to improve education and counseling about compost fertilizer in schools, as well as its important role in increasing students' awareness of environmental issues and sustainable agriculture. This research contributes to the understanding of students' level of knowledge regarding compost fertilizer and highlights the importance of education about sustainable agricultural practices at the secondary education level. Further efforts can be made to increase students' understanding of compost and its impact on the environment and agriculture. With a better understanding of compost, students can become agents of change who play a role in protecting and caring for our environment, as well as supporting more sustainable agriculture.